Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s00464-017-5827-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefits of single-incision laparoscopic surgery for postoperative delirium in elderly colon cancer patients

Abstract: SLS for elderly colon cancer patients may lower the incidence of POD compared with CLS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
0
12
2
1
Order By: Relevance
“…There are many factors affecting delirium after surgery, and pain is one of the factors [18]. Studies have shown that low IAP can reduce pain in patients during laparoscopic surgery [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…There are many factors affecting delirium after surgery, and pain is one of the factors [18]. Studies have shown that low IAP can reduce pain in patients during laparoscopic surgery [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…The application of SPLC in elderly patients remains controversial. To our knowledge, only two studies to date, both published in 2018, have specifically evaluated the outcomes of SPLC in elderly patients with colon cancer . One of these studies found no difference in outcomes between 86 elderly patients and 40 young patients who underwent SPLC for colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only two studies to date, both published in 2018, have specifically evaluated the outcomes of SPLC in elderly patients with colon cancer. 6,11 One of these studies found no difference in outcomes between 86 elderly patients and 40 young patients who underwent SPLC for colon cancer. However, the authors of that study identified a limitation: potential bias toward the surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…The alpha level and power were set to 0.05 and 0.8, respectively. According to previous pilot tests [ 28 , 29 ], the incidence of the primary outcome was 30%. After calculation, an average of 47 patients was required in each group.…”
Section: Methodsmentioning
confidence: 99%